Combined statin-fibrate therapy-induced rhabdomyolysis: Case report - Jozić Tanja L.; Terzić Branka M.; Mitrović Predrag M.; Kostić Jasminka D.; Milanov Marko Z.; Stojanović Milena M.; Ašanin Milika R. (Srpsko lekarsko drustvo, 2014)
Introduction Rhabdomyolysis is a rare, but serious and potentially fatal adverse reaction of the statin application that may be developed in any time of therapy. It is characterized by massive destruction of muscles associated with the large increase of creatine kinase (CK) leading to myoglobinuria and potential acute renal failure. Combined statin-fibrate therapy increases the risk of rhabdomyolysis, especially in elderly and diabetic patients. Case report An 81-year-old male was admitted to Coronary Care Unit of the Emergency Center, Clinical Center of Serbia (CCS) with the clinical picture and electrocardiogram of the acute anterior wall myocardial infarction complicated with pulmonary edema. Laboratory tests on admission showed higher elevated values of serum creatinine 179 μmol/L and BUN 9.2 mmol/L (eGFR 32 mL/min/1.73m2), CK 309 U/L (on day 2: 3476 U/L) and mixed hyperlipidemia (total cholesterol 10.3 mmol/L, HDL 2.26 mmol/L, TG 4.85 mmol/L). The patient was treated with thrombolysis medication therapy (Alteplase), anticoagulant and dual antiplatelet therapy, diuretics, organic nitrates, angiotensin-converting enzyme (ACE) inhibitors, antibiotics, and proton pump inhibitors. During seven days, his therapy included combined pravastatin 20 mg and fenofibrate (160 mg), which was discontinued due to pains and weakness of muscles and significantly elevated CC to 7080 U/L (upper limit 200 U/L), but no significant deterioration of renal function was observed. Discontinuation of therapy resulted in CC level normalization and improvement of clinical condition. Conclusion Combined statin and fibrate therapy requires strict clinical control and monitoring of CK i transaminases. Four-time or higher increase of CK requires discontinuation of therapy. In addition, patients are advised to report immediately any pains in muscles, sensibility, weakness or cramps.